2018
DOI: 10.3389/fpubh.2018.00278
|View full text |Cite
|
Sign up to set email alerts
|

Forest Walking Affects Autonomic Nervous Activity: A Population-Based Study

Abstract: The present study aimed to evaluate the effect of walking in forest environments on autonomic nervous activity with special reference to its distribution characteristics. Heart rate variability (HRV) of 485 male participants while walking for ~15 min in a forest and an urban area was analyzed. The experimental sites were 57 forests and 57 urban areas across Japan. Parasympathetic and sympathetic indicators [lnHF and ln(LF/HF), respectively] of HRV were calculated based on ~15-min heart rate recordings. Skewnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 32 publications
6
73
0
Order By: Relevance
“…Mental health benefits have been shown for many different types of adventurous outdoor recreation ( Araújo et al, 2019 ; Buckley, 2018a ; Collins & Brymer, 2018 ; Frühauf et al, 2016 ; Hansson et al, 2019 ; Hetland, Kjelstrup, Mittner, & Vitterso, 2019 ; Holland, Powell, Thomsen, & Monz, 2018 ; Holmbom, Brymer, & Schweitzer, 2017 ; Morris & Scott, 2019 ; Niedermeier et al, 2017 ; Roberts, Jones, & Brooks, 2018 ; White et al, 2016 ). Benefits have also been demonstrated for contemplative outdoor activities, such as forest walks ( Chen, Yu, & Lee, 2018 ; Hansen, Jones, & Tocchini, 2017 ; Kobayashi et al, 2018 ; Lyu et al, 2018 ; Morita et al, 2007 ; Oh et al, 2017 ). There is a parallel field of geographical research on therapeutic landscapes ( Bell, Foley, Houghton, Maddrell, & Williams, 2018 ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Mental health benefits have been shown for many different types of adventurous outdoor recreation ( Araújo et al, 2019 ; Buckley, 2018a ; Collins & Brymer, 2018 ; Frühauf et al, 2016 ; Hansson et al, 2019 ; Hetland, Kjelstrup, Mittner, & Vitterso, 2019 ; Holland, Powell, Thomsen, & Monz, 2018 ; Holmbom, Brymer, & Schweitzer, 2017 ; Morris & Scott, 2019 ; Niedermeier et al, 2017 ; Roberts, Jones, & Brooks, 2018 ; White et al, 2016 ). Benefits have also been demonstrated for contemplative outdoor activities, such as forest walks ( Chen, Yu, & Lee, 2018 ; Hansen, Jones, & Tocchini, 2017 ; Kobayashi et al, 2018 ; Lyu et al, 2018 ; Morita et al, 2007 ; Oh et al, 2017 ). There is a parallel field of geographical research on therapeutic landscapes ( Bell, Foley, Houghton, Maddrell, & Williams, 2018 ).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…In another of our previous studies (38), the effect of walking in a forest environment and the effect of viewing a forest landscape on HRV indices was investigated. In the study, a positive responder was defined as a participant who exhibited an increase in log-transformed high-frequency component (lnHF).…”
Section: Forest-walking Vs Forest-viewingmentioning
confidence: 99%
“…In addition to many studies targeting healthy young men, studies including large sample sizes [9,16] and population-based studies, have also been reported [17,18,19]. In a study involving 420 participants, Park et al [16] demonstrated that forest therapy mitigated stress and led to physiological relaxation, as evidenced by the index of heart rate variability (HRV), blood pressure, pulse rate, and salivary cortisol concentration.…”
Section: Introductionmentioning
confidence: 99%